English communicative competence and predominant language for online use through smartphones in Croatia as compared to Slovenia - Varga Mirna; Jurkovič Violeta; Sierocka Halina (ExELL (Explorations in English Language and Linguistics))
The study explores which languages are predominant in the online use among the targeted participant population in Croatia and Slovenia and examines the association between the participants’ smartphone online use of English and preferred subtitling mode with their perceived communicative competence in English. The findings indicate that in both nationality groups the use of English prevails in receptive language activities, in particular listening and audio-visual reception, while mother tongues are mainly used for productive and interactive activities. Participants who prefer English when engaging in online informal activities through their smartphones and who use English or no subtitles when watching video content also assess their competence in English to be on higher levels.